2006
DOI: 10.1063/1.2358696
|View full text |Cite
|
Sign up to set email alerts
|

Temperature compensation of Wheatstone bridge magnetoresistive sensors based on generalized impedance converter with input reference current

Abstract: A compensation method of the sensitivity drift of the Wheatstone bridge sensor is proposed. The technique was carried out by placing a temperature sensor and the bridge to be compensated inside a generalized impedance converter with input reference current. No internal modification of the bridge arms is required so that the circuit is capable to compensate practical industrial sensors. The method is based on the temperature modulation of the current supplied to the bridge, which improves previous solutions bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Usually finite frequency of the crossover frequency f c is considered as some non-ideality of an OpAmp but the purpose of the present paper is to demonstrate that this inequality can be used for something useful, to design and create tunable high-Q resonators for various applications. [25][26][27][28] In other words, the novelty of the proposed scheme is based on the immanent property of the operational amplifiers -the finite crossover frequency f c . Recently we have also developed a method for fast and accurate measurement of the crossover frequency of operational amplifiers.…”
mentioning
confidence: 99%
“…Usually finite frequency of the crossover frequency f c is considered as some non-ideality of an OpAmp but the purpose of the present paper is to demonstrate that this inequality can be used for something useful, to design and create tunable high-Q resonators for various applications. [25][26][27][28] In other words, the novelty of the proposed scheme is based on the immanent property of the operational amplifiers -the finite crossover frequency f c . Recently we have also developed a method for fast and accurate measurement of the crossover frequency of operational amplifiers.…”
mentioning
confidence: 99%
“…The conventional full-bridge circuit itself can also be modified to improve temperature compensation and reduce thermal drift output. Non-invasive bridge manipulation techniques involve the addition of different circuit elements to the full-bridge system, whereas invasive techniques require the modification of the initial bridge elements (Munoz et al 2006). Furthermore, several studies have improved temperature compensation in their measurements by implementing not one, but two bridge circuits in their experiments.…”
Section: Full-bridge Circuitsmentioning
confidence: 99%
“…Meanwhile, the hardware method has advantages in real-time perform sensor with simple temperature drift behavior, the hardware method has advantages in real-time. Other research groups have reported the temperature dependence and compensation methods for AMR devices with Wheatstone bridge (Kim et al , 2000; Ripka et al , 2003; Ramirez Munoz et al , 2006; Vopalensky and Platil, 2013; Harmon et al , 2015), and there is still no relevant work on spin-valve sensor. In this paper, the temperature properties of spin-valve sensor are thoroughly investigated, and experimental results and compensation technique are presented.…”
Section: Introductionmentioning
confidence: 99%